Phosphorylation of a member of the MBF1 transcriptional co-activator family, StMBF1, is stimulated in potato cell suspensions upon fungal elicitor challenge - Zanetti, María Eugenia (2003)
StMBF1 (Solanum tuberosum multiprotein bridging factor 1) is a plant member of the MBF1 family of transcriptional co-activators. Previously, it has been described as being up-regulated at the transcriptional level by fungal and abiotic stress. To understand whether StMBF1 is also regulated at the post-- translational level, in vitro as well as in vivo phosphorylation assays were performed. StMBF1 is phosphorylated under both experimental conditions and [32P] incorporation into StMBF1 increases after treatment of potato cells with hyphal cell wall components (HWC) derived from Phytophthora infestans. The StMBF1-phosphorylating activity is strongly inhibited by the calcium-chelator EGTA and partially inhibited by calmodulin antagonists. Using bacterial puri®ed StMBF1 as a substrate, a 57 kDa calcium-dependent protein kinase (p57) that is able to phosphorylate StMBF1 was detected. The StMBF1 kinase activity of p57 was higher in elicited than in non-treated cells. The role of the elicitor-dependent phosphorylation of StMBF1 is discussed